(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
The bioassay activitiesofTithonia diversifolia leave extract was conducted on the larvae of Anopheles mosquito collected at peri-urban areas of Abakaliki Ebonyi State, using the concentrations of the extract in dilutions at 50/100ml, 40/100ml, 30/100ml and 20/100ml introduced with 10 Anopheles mosquito larvae each in four replicates and allowed for 3hrs. Mean mortality rate of the larvae were observed after the first hour, thus 30%, 10%, 05% and 0% respectively while in the 2nd hour were 60%, 40%, 20% and 10% and in the 3rd hour were 80%, 60%, 50% & 30% respectively. The result thus revealed that the treatment is dose dependent and that the studied specie has some bioactive compounds that can be exploited for insect pests control hence observed to be sensitive in anopheles mosquito larvae. Therefore Tithonia diversifolialeaf extract could be used as a bioassay for the control of mosquito due to its active properties as this has exhibited adverse effects on the larvae thereby reducing the mosquito population and thus reducing the malarious infection associated with the bite of mosquito.